1997
DOI: 10.1515/znc-1997-5-604
|View full text |Cite
|
Sign up to set email alerts
|

Exudate Flavonoids in Asteraceae from Arizona, California and Mexico

Abstract: A steraceae, A stereae, Eupatorieae, Helenieae, Heliantheae, Exudate Flavonoids A series of A steraceae, belonging to the tribes Astereae, Eupatorieae, Helenieae and Heli antheae, have been analyzed for the presence of flavonoid aglycones accumulated on leaf and stem surfaces. Methyl ethers of apigenin, luteolin, kaempferol, and quercetin as well as methyl ethers of their relevant 6 -hydroxy derivatives were abundant, whereas 8 -O-substituted derivatives and flavanones were encountered only occasionally; 6 ,8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Gray, while E. staechadifolium Lag. yielded qu/-3-Me/-3Ј-Me/ -3,3Ј-diMe; queg-3,6-diMe/-3,6,3Ј-triMe (Wollenweber et al, 1997b). Apart from these results, no further flavonoid data are available on this genus.…”
Section: Flavonoid Aglycones Of Helenieae Speciesmentioning
confidence: 89%
See 3 more Smart Citations
“…Gray, while E. staechadifolium Lag. yielded qu/-3-Me/-3Ј-Me/ -3,3Ј-diMe; queg-3,6-diMe/-3,6,3Ј-triMe (Wollenweber et al, 1997b). Apart from these results, no further flavonoid data are available on this genus.…”
Section: Flavonoid Aglycones Of Helenieae Speciesmentioning
confidence: 89%
“…Therefore, § Part V in the series "Exudate Flavonoids in Miscellaneous Asteraceae". For Part IV see Wollenweber et al (2005), for Part III see Wollenweber et al (1997b). Earlier, we have shown that some accumulation tendencies apparently exist in single tribes (Wollenweber and Valant-Vetschera, 1996).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…-Extensive chromatographic purification of the petroleum ether/Et 2 O/MeOH 1 : 1 : 1 extract of the whole plant of Aster himalaicus led to the isolation of a new eudesmane sesquiterpene, 1-oxoeudesm-11(13)-eno-12,8a-lactone (1), along with twelve known compounds, including ilicic acid (2) [9], (7aH)-3-oxoeudesma-4,11(13)-dien-12-oic acid (3) [10], (5a,7aH)-2-oxoeudesma-3,11(13)-dien-12-oic acid (4) [11], luteolin (5) [12], 5,6-dihydroxy-3,7,4'-trimethoxyflavonol (6) [13], 5,6,3'-trihydroxy-3,7,4'-trimethoxyflavonol (7) [14], 5,6-dihydroxy-3,7,3',4'-tetramethoxyflavonol (8) [15], b-sitosterol, 3,4-dihydroxybenzaldehyde [16], p-hydroxybenzoic acid methyl ester [17], 3,4-dihydroxybenzoic acid [17], and 4-hydroxy-3-methoxybenzoic acid [17]. b-Sitosterol was identified on the basis of melting point and TLC comparison with an authentic sample.…”
mentioning
confidence: 99%